COMMAND, CONTROL, AND COMMUNICATION: A STUDY OF MILITARY SYNTAX (SCIENCE TIME JOURNAL, 2026)
This article examines the role of syntax in military discourse, focusing on its communicative functions and structural characteristics. Military speech is presented as a specialized form of language shaped by the need for clarity, brevity, and operational efficiency. The study analyzes key syntactic features, including the use of imperative constructions, subject-verb-object structures, and hierarchical patterns in command formulation. Particular attention is given to the role of jargon and acronyms in enhancing communicative precision and group cohesion within military environments. The findings demonstrate that syntax in military discourse is not only a structural element but also a functional tool that supports effective command, control, and interaction among personnel.